Mathematical Modeling of Teenage Pregnancy Focused on Awareness and Behavioral Change - Rachel Basanez Apdo; Rolly Najial Apdo; Iranly Tavera Gumombal (Jambura Journal of Biomathematics (JJBM), 2025)
Teenage pregnancy remains a signiﬁcant public health concern, particularly in the Philippines.   This study extends a previous SIT model by introducing a behavioral relapse pathway (Ω) that represents the rate at which informed adolescents revert to risky sexual behavior.   The model divides the population into susceptible, corrupted, and aware compartments, incorporating contraceptive use and sex education.   Analytical results show that the corruption-free equilibrium is locally asymptotically stable when R0       1,  while  corruption persists when R0     1.  Numerical simulations reveal that increasing Ω from 0.01 to 0.2 raises the long-term corrupted population fraction from approximately 8% to more than 25% with transient peaks up to 22%, even with high awareness levels. A local sensitivity analysis further reveals that the recruitment rate (ω), voluntary cessation rate (π), and natural death rate (µ) exert the greatest inﬂuence on long-term outcomes. These ﬁndings highlight that sustained awareness campaigns must be coupled with strategies that minimize relapse into risky behavior, such as continuous sex education, peer mentorship, and counter-misinformation initiatives.